Perbaikan Dip Tegangan pada Motor Menggunakan Kompensasi Kapasitif dan Beban Tiruan - Tiyono (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2012)
Quality of voltage stability both in industrial and residence electricity services really becomes a continuity and reliability system demand. But high industrial load, such as motor, welding machine, electric furnace, other high power supply make a flicker or even a voltage dip. The dip affects not only the user, but also the the distribution network, with the result that disturbs other users on the outside of the area. A method decreasing the dip effect is by using voltage compensator, which is a volt ampere rective compensation (VAR-Compensation) injected to load in parallel network.In this paper, VAR on motor load will be investigated. The compensator consists of a capacitor bank A with full of charge in the beginning condition as a compensator and a capacitor bank B with no charge in the beginning condition as a dummy load. The compensator is expected working while before the system is back to normal condition (stable) that is done by either AVR or the generator governor. For example, a high power motor is connected to the network. In the network, ther will be a voltage dip. If in conjunction with the motor to be attached along with the interlinked network of capacitor A and the capacitor A is off again after the normal voltage. Similarly, when the release of the motor, also comes with the inclusion of capacitor B to the network and capacitor B is off again after a normal system voltage.Actually, this compensation method applies past method, for example SVC (Static VAR Compensation). VAR value calculation which is appropriate with starting power motor becomes an attention in this paper. This paper is fully new which is idea and logic.